Low fundamental movement skill proficiency is associated with high BMI and body fatness in girls but not boys aged 6–11 years old. Issue 21 (2nd November 2017) - Duncan, Michael J.; Bryant, Elizabeth; Stodden, David
ABSTRACT: This study examined differences in children's body mass index (BMI) and body fatness (BF%) as a function of gender and fundamental movement skill (FMS) proficiency. Following ethics approval and parental consent, 248, 6–11 year-old children (112 boys, 136 girls) underwent assessment of 7 FMS: sprint run, side gallop, hop, kick, catch, throw and vertical jump. FMS tertiles ("high", "medium" or "low" FMS) were created based on the summed components of the FMS. Skinfold measures were used to calculate BF%. Physical activity (PA) was assessed using pedometry and maturation predicted using anthropometry. Data were analysed using a 2 (Gender) × 3 (FMS tertile) ways analysis of covariance (ANCOVA), controlling for age, maturation and PA. Age ( P = .001) and maturation ( P = .006) were associated with BMI. Girls classified as high FMS proficiency had significantly lower BMI compared to girls with low and medium FMS proficiency. Age ( P = .0001) and maturation ( P = .007) were associated with BF%. BF% was also higher for girls with low FMS compared to those with medium and high FMS. BF% and BMI were not different across FMS tertile in boys. Such findings suggest focusing on FMS may be especially important for healthy weight, particularly in girls.